2002
DOI: 10.4049/jimmunol.168.3.1348
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 Is Required for Antibody-Mediated Protective Immunity Against Blood-StagePlasmodiumchabaudiAS Malaria Infection in Mice

Abstract: In this study, we investigated the role of endogenous IL-12 in protective immunity against blood-stage P. chabaudi AS malaria using IL-12 p40 gene knockout (KO) and wild-type (WT) C57BL/6 mice. Following infection, KO mice developed significantly higher levels of primary parasitemia than WT mice and were unable to rapidly resolve primary infection and control challenge infection. Infected KO mice had severely impaired IFN-γ production in vivo and in vitro by NK cells and splenocytes compared with WT mice. Prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
143
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(160 citation statements)
references
References 50 publications
13
143
1
3
Order By: Relevance
“…Thus, CD8 + DC may not only be crucial for initiation of CD8 + T cell responses leading to ECM, but also for promoting Th1 cell development that in turn facilitates IFN-g-dependent CD8 + T cell recruitment to this organ. Alternatively, control of P. chabaudi infection largely requires Th1 cells during the first peak of parasitemia (84) and Tfh cells for complete elimination of the parasite (85). Tfh cells secrete several cytokines, such as IFN-g, IL-2, IL-4, and IL-21.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CD8 + DC may not only be crucial for initiation of CD8 + T cell responses leading to ECM, but also for promoting Th1 cell development that in turn facilitates IFN-g-dependent CD8 + T cell recruitment to this organ. Alternatively, control of P. chabaudi infection largely requires Th1 cells during the first peak of parasitemia (84) and Tfh cells for complete elimination of the parasite (85). Tfh cells secrete several cytokines, such as IFN-g, IL-2, IL-4, and IL-21.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that the predisposing locus may not be located within the peak of linkage and that there is accumulating evidence for a role of IL12 in malaria. [13][14][15][16][17][18][19] We, therefore, searched for IL12B polymorphisms in the whole coding sequence, including the intron-exon borders, and genotyped cis-regulatory polymorphisms within the promoter and the 3 0 UTR region in individuals living in an endemic area. We did not find any polymorphism within the coding sequence, indicating a high level of conservation of IL12B in African populations, as previously suggested in Caucasian populations.…”
Section: Il12b In Human Malariamentioning
confidence: 99%
“…13,14 Studies with IL-12p40-deficient mice confirmed the effect of IL-12 in the protection against P. chabaudi. 15,16 In humans, low levels of IL-12 have been associated with severe malaria 17,18 and increased parasitemia. 19 In addition, a promoter polymorphism in IL12B (rs17860508), which is thought to influence the production of IL-12, 20,21 was associated with increased mortality from cerebral malaria in Tanzanian children.…”
Section: Introductionmentioning
confidence: 99%
“…Bloodstage malaria infections were initiated by i.p. injection of 1 × 10 6 pRBCs and parasitemia was monitored daily by examination of Giemsa-stained (Sigma-Aldrich, MO, USA) thin smears of tail blood [35]. The infected mice were monitored closely.…”
Section: Mice and Parasitesmentioning
confidence: 99%